Sistem Pakar Mendiagnosa Penyakit Gigi dan Mulut Menggunakan Metode Naive Bayes - Erika Novianti; Jonson Manurung (Pustaka Timur Publisher, 2021)
Technological advances that are growing rapidly are very beneficial for humans in completing their work. The high cost of consulting and checking teeth or mouth makes residents reluctant to go to the doctor. Expert systems are also widely used by humans in the medical field, especially in this research. In order to facilitate the consultation, a system is needed that can predict the dental and oral diseases that he is suffering from without having to go to the doctor to consult the disease. An expert system is a system for human-to-computer knowledge, so that computers can solve problems such as those that are usually tried by experts. Experts defined here are people who have special abilities who can solve problems that ordinary people cannot solve. Research on dental and oral disease expert systems for the manufacture of this expert system used the Naive Bayes method. The decision to diagnose dental and oral disease is carried out through a consultation process between the system and the user, if the answers are entered according to applicable regulations, then the system will share the results of the diagnosis of dental and oral diseases that he suffers from. We recommend that the procedures for collecting data in conducting this research are: interviews and literature review. In making this expert system with the Naive Bayes method, it is hoped that it can help residents to identify diseases, or provide solutions to problems with their teeth and mouth without having to go to the doctor first.